46.7k views
3 votes
Simplify. (−6)^2 please help

2 Answers

1 vote

Answer:


\huge \boxed{36}}

Explanation:

PEMDAS

Parenthesis

Exponent

Multiply

Divide

Add

Subtract


\displaystyle-6^2=6^2

Exponent, to find the answer.


\displaystyle6^2=6*6=36


\displaystyle 36, which is our answer.

User Bhav
by
5.8k points
5 votes

Note that (-6)^2 = (-6)(-6)

Multiply across. Remember that when multiplying two negative numbers, the product would be a positive answer

(-6) x (-6) = 36

36 is your answer

~Rise Above the Ordinary, Senpai


User Michael Heil
by
6.4k points